MicroRNA-17-92 Regulates Beta-Cell Restoration After Streptozotocin Treatment - Wan, Shan; Zhang, Jie; Chen, Xiang; Lang, Jiangli; Li, Li; Chen, Fei; Tian, Li; Meng, Yang; Yu, Xijie (Frontiers in Endocrinology, 2020)
Objective: To clarify the role and mechanism of miR-17-92 cluster in islet beta-cell repair after streptozotocin intervention. Methods: Genetically engineered mice (miR-17-92βKO) and control RIP-Cre mice were intraperitoneally injected with multiple low dose streptozotocin. Body weight, random blood glucose, fasting blood glucose, and intraperitoneal glucose tolerance test were monitored regularly. Mice were sacrificed for histological analysis eight weeks later. Morphological changes of pancreas islets, quantity, quality, apoptosis and proliferation of beta-cells were measured. Islets from four groups were isolated. MiRNA and mRNA were extracted and quantified. Results: MiR-17-92βKO mice showed dramatically elevated fasting blood glucose and impaired glucose tolerance after streptozotocin treatment in contrast to control mice, the reason of which is reduced beta-cell number and total mass resulting from reduced proliferation, enhanced apoptosis of beta-cells. Genes related to cell proliferation and insulin transcription repression were significantly elevated in miR-17-92βKO mice treated with streptozotocin. Furthermore, genes involved in DNA biosynthesis and damage repair were dramatically increased in miR-17-92βKO mice with streptozotocin treatment. Conclusion: Collectively, our results demonstrate that homozygous deletion of miR-17-92 cluster in mouse pancreatic beta-cells promotes the development of experimental diabetes, indicating that miR-17-92 cluster may be positively correlated to beta-cells restoration and adaption after streptozotocin-induced damage.